Поверхностная модификация гранулированных нитратов целлюлозы пластифицирующим веществом - Лукашев, В. К.; Онда, В. И.; Шевцова, Т. Н. (НТУ "ХПИ", 2016)
Проведено експериментальні дослідження, в результаті яких встановлено закономірності поверхневої модифікації пластифікуючою речовиною гранул, виготовлених лаковим способом зі складу на основі нітрату целюлози. На підставі одержаних даних запропоновано емпіричні залежності, які дозволяють розраховувати кількість дибутилфталату, що перейшло у нітратцеллюлозні гранули протягом заданого часу при обробці їх рідинним і емульсійним способом.

The experimental studies are conducted, as a result of that the regularities of the surface modification with the plasticizing substance of the granules made with the varnish method from the composition on the basis of cellulose nitrate are set. The empirical dependences for calculating the amount of dibutylphthalate which passed into the cellulose nitrate granules during the set time at treatment of their with liquid and emulsion method are offered based on the obtained data.
The surface modification of the granular cellulose nitrate with the plasticizing substance
Keywords: капиллярно-пористая система; диффузия; жидкостный способ; эмульсионный способ; дибутилфталат; гранулы